Use of a basal-plus insulin regimen in persons with type 2 diabetes stratified by age and body mass index: A pooled analysis of four clinical trials. Issue 1 (February 2016) - Lankisch, Mark R.; Del Prato, Stefano; Dain, Marie-Paule; Mullins, Peter; Owens, David R.
Highlights: Retrospective analysis to evaluate a 'basal-plus' regimen in type 2 diabetes. Glycated hemoglobin (HbA1c) and post-prandial glucose decreased at 6 months. Proportion of subjects with HbA1c < 7% increased. Prevalence of severe hypoglycemia was low and did not differ across groups. Neither age nor body mass index influenced the findings. Abstract: Aims: To evaluate the efficacy and safety of adding a single bolus dose of insulin glulisine to basal insulin ('basal-plus') in persons with type 2 diabetes. Methods: Data from patients with poor glycemic control on oral antihyperglycemic drugs who were initiated on a 'basal-plus' regimen for up to 6 months were pooled from four randomized, multicenter studies. Glycated hemoglobin (HbA1c), fasting blood glucose, postprandial glucose (PPG), insulin dose and demographics were measured at baseline and end of study. Results: 711 patients with a mean age of 59.9 years and a mean duration of diabetes of 11.0 years were included in the analysis population. A 'basal-plus' regimen was associated with significant decreases in HbA1c and PPG at 6 months, an increase in glargine and glulisine doses and small, but statistically significant, changes in body weight and BMI in all patient subsets. The proportion of patients with HbA1c < 7% also increased in all populations studied, while the prevalence of severe hypoglycemia was low and did not significantly differ across patient groups. Conclusions: These results suggest that the use of 'basal-plus' can achieve a good therapeutic response with a low risk of hypoglycemia and weight gain, regardless of a patient's age or BMI.